An Evaluation of Haematological Changes in Paediatric Dengue Fever Patients at a Tertiary Care Hospital Rawalpindi During 2019 Outbreak - Rai Muhammad Asghar, Rai Rijjal Ashraf, Khalid Saheel, Abid Hussain, (Journal of Rawalpindi Medical College, 2021)
Objective: The study aimed to evaluate the hematological parameters of patients with dengue fever in order to increase the sensitivity of screening for early diagnosis and as an aid to the early institution of appropriate treatment. Materials and Methods: This study was conducted in Peadiatrics Department Benazir Bhutto Hospital, Rawalpindi for a period of 6 months from July 2019 to December 2019. Results: During the study period of 6 months, 438 dengue serology-positive children were admitted, amongst which 254 were male (58%), and 184 were female (42%). The children's age ranged from 1 month to 12 years, with a mean age of 8.03 years (SD + 3.13 years). Out of 438 children, 254 (58%) were uncomplicated dengue fever (DF), 119 children (27%) developed dengue hemorrhagic fever (DHF). 65 children (15%) went into dengue shock syndrome (DSS). The predominant findings in the complete blood picture (CBC) were Thrombocytopenia (80.1%) and leucopenia (65.1%). Normal leucocyte count was seen in 59 cases (13.68%). Thrombocytopenia (platelets less than 100,000) was seen in 351 patients (80.1%) out of which 30 cases (6.9%) had a platelet count less than 50,000. Leukopenia was found in 285 (65.1%) patients. Most of the patients were positive for NS1 (70.3%). IgM was positive in 62.1% and IgG was positive in 14.8%. Enteric Fever as co-infection was found in 30(6.8%) children. Conclusion: Careful assessment and interpretation of hematological changes in dengue patients allow early diagnosis and institution of appropriate treatment.